Vasorelaxant effects of Angelica decursiva root on isolated rat aortic rings - Bumjung Kim; Youngki Kwon; Somin Lee; Kyungjin Lee; Inhye Ham; Ho-Young Choi (BMC, 2017)
Abstract Background Hypertension is one of the most important risk factors for cardiovascular disease (CVD) and a worldwide problem. Despite increases in the development of synthetic drugs for hypertension treatment, the rate of untreated and uncontrolled hypertension remains high. These drugs are effective, but can also cause side effects. Approximately 80% of the world population uses herbal medicines because of their low toxicity and better acceptability by the human body. Therefore, we attempted to identify natural medications for treating hypertension. The 70% ethanol extract of Angelica decursiva root (ADE) shows strong vasorelaxant potential, but no studies have investigated the mechanisms underlying the vasorelaxation effect of A. decursiva. Methods Dried root of A. decursiva was identified by DNA sequencing and was extracted once with 1 L 70% ethanol (EtOH) for 3 h in a reflux apparatus at 70 °C. ADE was evaluated for its vasorelaxant effects in rat thoracic aortas. Various inhibitors of ADE-induced vasorelaxation were used. Results ADE showed vasorelaxant effects on the intact and denuded endothelium of aortic rings pre-contracted with phenylephrine and KCl in Krebs-Henseleit solution. Tetraethylammonium and 4-aminopyridine did not alter ADE-induced vasorelaxation. However, the vasorelaxant effect of ADE was partially inhibited by pre-treatment with glibenclamide an ATP-sensitive K+ channel blocker. Furthermore, ADE concentration-dependently inhibited Ca2+ supplementation-induced vasoconstriction of aortic rings that had been pretreated with phenylephrine or KCl in Ca2+-free Krebs-Henseleit solution. Conclusions These results suggest that ADE-induced vasorelaxation occurred in an endothelium-independent manner. The vasorelaxant effects of ADE were correlated with blockade of the KATP channel and inhibition of Ca2+ influx via receptor-operative Ca2+ channels or voltage-dependent Ca2+ channels.